Distribution and antifungal susceptibility pattern of Candida species at a tertiary hospital in Malaysia - Mohamed N.A.; Hussin H.; Zaini A.B.; Siva Gowri a/p Pathmanathan (Journal of Infection in Developing Countries, 2024)
Introduction: Invasive Candida infections cause significant mortality and morbidity worldwide. Information on recent trends in species distribution and antifungal resistance in local settings is essential. Methodology: Yeast isolates identified through standard culture methods throughout 2014 and 2015 from Hospital Ampang, Malaysia were retrospectively studied. The antifungal susceptibility of Candida species was determined using colorimetric broth microdilution method and MIC values interpreted according to CLSI breakpoints. Results: Out of all the 149 yeast cultures collected, most were from blood (55.7%) and respiratory specimens (33.6%). Candida tropicalis was the most common (28.9%), followed by C. albicans (26.2%), C. parapsilosis (15.4%), C. glabrata (14.1%), Crytococcus neoformans (6.7%), Trichosporon asahi (3.4%), C. krusei (2.0%), C. famata, C. rugose, C. guilliermondii, C. dublinensis and Trichosporon spp. (0.7% each). Occurrence of C. tropicalis in candidaemia cases was significantly associated to presence of an underlying haematological disorder, while C. albicans isolates in blood were significantly found in absence of such disorders. The four most common Candida species isolated showed high susceptibility to amphotericin B (100%), anidulafungin (100%), micafungin (100%), caspofungin (98.4%), flucytosine (98.4%) and voriconazole (84.1%). However, drug susceptibility to itraconazole and fluconazole was comparatively lower (57.9% and 72.2%, respectively). C. glabrata and C. tropicalis were the least susceptible to these azoles. Conclusion: Prevalence of the high number of non-albicans Candida species with slight predominance of C. tropicalis over C. albicans was observed. Low susceptibility to itraconazole among C. glabrata and C. tropicalis isolates and to fluconazole among C. glabrata isolates warrants for continued surveillance to monitor emerging antifungal resistance.